Proceedings of 2012 3rd International Asia Conference on Industrial Engineering and Management Innovation (IEMI2012) - Dou, Runliang; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The purpose of the 2012 3rd International Asia Conference on Industrial Engineering and Management Innovation (IEMI2012) is to bring together researchers, engineers and practitioners interested in the application of informatics to usher in new advances in the industrial engineering and management fields.
Core areas of Industrial Engineering -- Assistive Technology of Industrial Engineering -- Management System Innovation or Areas of engineering education.
Keywords: Economics; Industrial engineering; Management information systems; Economics/Management Science; Economics/Management Science, general; Industrial and Production Engineering; Innovation/Technology Management; Business Information Systems